2020
DOI: 10.21595/mme.2020.21241
|View full text |Cite
|
Sign up to set email alerts
|

Development of cab isolation systems of off-road vibratory rollers: review research

Abstract: To have an overview of the research and development processes of the cab isolation system of the off-road vibratory rollers, this paper represents the researches of the various isolation systems based on the previously studied and published results. The result has shown that the ride comfort is mainly improved by the cab isolation system used the semi-active hydraulic mounts. The paper results can provide the overall view of the vibration studies of the off-road vibratory rollers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In previous researches, the vibration of vibratory rollers was mainly solved in the time region on improving the ride comfort [1][2][3][8][9], the acceleration-frequency characteristic of the isolations of the cab and the vehicle in the frequency region gets very little attention. In this study, the acceleration-frequency characteristic of isolations is studied to analyze the results.…”
Section: Vehicle Model and Vibration Equation In The Time Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous researches, the vibration of vibratory rollers was mainly solved in the time region on improving the ride comfort [1][2][3][8][9], the acceleration-frequency characteristic of the isolations of the cab and the vehicle in the frequency region gets very little attention. In this study, the acceleration-frequency characteristic of isolations is studied to analyze the results.…”
Section: Vehicle Model and Vibration Equation In The Time Regionmentioning
confidence: 99%
“…The cab isolation system of the vibratory rollers was used to reduce the transmission vibration from the vibrator drum and the road surface to the driver [1]. In the previous researches of vibratory rollers showed that the vehicle's ride comfort was strongly affected by the vibration excitations of the drum and road surface [1][2][3], thus, the cab isolations were continuously researched and developed. The structure of the traditional rubber mounts equipped on the vibratory roller cab was re-designed and optimized to improve the ride comfort [2].…”
Section: Introductionmentioning
confidence: 99%